Ответы 1

  • Ответ:

    Пошаговое объяснение:

    y=x³-3x²-45x+1    [-4;6]

    y'=3x²-6x-45=0

    3x²-6x-45=0  |÷3

    x²-2x-15=0    D=64      √D=8

    x₁=-3        x₂=5    ⇒

    y(-4)=(-4)³-3*(-4)²-45*(-4)+1=-64-48+180+1=69.

    y(-3)=(-3)³-3*(-3)²-45*(-3)+1=-27-27+135+1=82=унаиб.

    y(5)=5³-3*5²-45*5+1=125-75-225+1=-174=yнаим.

    y(6)=6³-3*6²-45*6+1=216-108-270+1=-161.

    • Автор:

      sarahf9bv
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years